2015
DOI: 10.5539/ibr.v8n6p89
|View full text |Cite
|
Sign up to set email alerts
|

Universal Values, Creative Behavior and Leadership: Turkish Case

Abstract: Organizational creativity has become one of the major research areas in the field of organizational behavior during the last two decades. This paper aims to provide a better understanding of the association between universal individual values and employee creative behavior and explores the mediating effect of leadership on the relationship between individual values and employee creative behavior. The research sample was chosen from service sector employees owing to the fact that the role of leadership and moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…From these results over regression, the fourth hypothesis is therefore rejected. These results are thus in line with results of existing studies (Khan, Aslam & Riaz, 2012;Wu & Lin, 2018;Carlo, Jean & Boudrias, 2015;Kurt & Yahyagil, 2015;Eisenbeiss, Knippenberg & Boerner, 2008;Kwasi & Emmanuel, 2015;Mukherjee & Ray, 2009). Consequently, the existing literature hence provides significant support to the results of the present study.…”
Section: Hsupporting
confidence: 93%
See 1 more Smart Citation
“…From these results over regression, the fourth hypothesis is therefore rejected. These results are thus in line with results of existing studies (Khan, Aslam & Riaz, 2012;Wu & Lin, 2018;Carlo, Jean & Boudrias, 2015;Kurt & Yahyagil, 2015;Eisenbeiss, Knippenberg & Boerner, 2008;Kwasi & Emmanuel, 2015;Mukherjee & Ray, 2009). Consequently, the existing literature hence provides significant support to the results of the present study.…”
Section: Hsupporting
confidence: 93%
“…Academic leadership is important in motivation, and effectiveness towards the entire system of higher education (Siddique, Aslam, Khan & Fatima, 2011). Transformational leadership is effective in determining the needs and motivation of the employees through the transformational process towards the desired objectives wherein the efforts, values, and potential are highly recognized (Kurt & Yahyagil, 2015). Transactional leadership is vital in determining the desired values and efforts through an exchange process wherein reward and The innovative work behavior is the outcome of various efforts on the part of employees, leadership and institution as it is critical to recognize the factors that promotes followers' innovative work behavior (Škudienė, Augutytė, Demeško & Suchockis, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have shown paternalistic leadership to pave the way for adverse outcomes such as leader bullying (Soylu, 2011) or higher turnover (Liao, Widowati, Hu, & Tasman, 2017), they have also shown PL to be able to lead to positive employee behaviors such as creativeness (Kurt & Yahyagil, 2015) and organizational citizenship behaviors (Mete & Serin, 2015) as well as positive attitudes such as job satisfaction (Nal & Tarım, 2019) and organizational commitment (Erben & Güneşer, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Self‐reported creativity of frontline‐service employees in a large bank in Portugal correlated positively with openness to change versus conservation values (Sousa & Coelho, ). Similarly, self‐reported creativity correlated positively with self‐direction values and negatively with conformity values among employees from diverse industries in Egypt (Rice, ), and it correlated positively with self‐direction values among members of service organisations in Turkey (Kurt & Yahyagil, ).…”
Section: Value Profile Of Managersmentioning
confidence: 99%